PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL DAN MEDIA AUDIO VISUAL BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR MAHASISWA UNIVERSITAS PGRI PALEMBANG - Topan, Muhammad; Fitriani, Yessi; Utami, Puspa Indah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
The research aims to look at the influence of contextual learning models and audio-visual media based on local wisdom on the learning outcomes of Indonesian language education students at the PGRI University of Palembang. This type of research is quantitative research that uses simple linear regression testing and multiple linear regression testing to answer the hypothesis in the research. The samples in this research were semesters 3A and 3B as experimental classes with 20 students each. This research data collection technique uses test and questionnaire techniques, observation and documentation. Based on the results of the study, there is an influence which states that Ho is rejected. Testing the first hypothesis obtained the effect of applying the contextual learning model which obtained a significant value of 0.943. The results of testing the second hypothesis show the influence of audio-visual media based on local wisdom on learning outcomes with a significant value of 0.369. The results of testing the third hypothesis prove that there is an influence of the application of contextual learning models and audio-visual media based on local wisdom on learning outcomes which obtained a significant value of 0.669.